Multivariate analysis in wheat germplasm captures variability for agro-morphological and physiological traits - KUMAR, SATISH; GUPTA, VIKAS; YADAV, SONU SINGH; M, MAMRUTHA H; SINGH, SANJAY KUMAR; CHATRATH, RAVISH; SINGH, GYANENDRA PRATAP (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out with an objective to investige genetic diversity in set of diverse wheat genotypes during 2018-19 at the experimental farm of Indian Institute of Wheat and Barley Research, Karnal. Principal Component Analysis was carried out on this set of 440 genotypes to study variability for different agro-morphological and physiological traits. The coefficient of variation ranged from 7.20-38.30 for the measured traits. Yield per plot was positively related with tillers per m, spike length, grains per spike and 1000 grains weight. The first three principal components explained 45.66% of variation. Agglomerative clustering grouped the genotypes into six groups and had a cophenetic correlation coefficient of 0.319. Almost all the components explained some variation for each trait and hence can be further used in hybridization for creation of variability in the breeding programs to develop improved cultivars. This remarkable variation in the set can be accounted to the fact that these lines were a collection of germplasm from different wheat growing countries and also their specificity for different traits.